Reconsidering Deuteronomy 26:5–11 as a "small historical creed": Overtures towards a "migrant reading" within the Persian period - Bosman, Hendrik Ludolph (HTS teologiese studies, 2019)
Against the backdrop of recent scholarship related to Deuteronomy 26:5–11, the influential hypothesis formulated by Gerhard von Rad that this verse entails a ‘small historical creed’ will be re-evaluated. In addition to recent Old Testament scholarship, attention will be paid to migrant theory and a rereading of 26:5–11. It will be suggested that this ‘creed’ addressed the identity concerns of returning migrants or exiles from Babylon, as well as the peasant farmers who remained behind in Palestine. Thus, the creed is not understood as an early cultic starting point of a theological tradition, but as a later synthesising framework that responded to theological challenges and tensions prevalent in Persian Yehud.